Controllable Synthesis of Flower-like Hierarchical CuCo2S4 Nanostructure Arrays for High-Performance Hybrid Supercapacitors - Man Li; Ningning Yu; Lei Xu; Wenyu Wang; Fuxiang Wei; Jiqiu Qi; Yanwei Sui (Metals, 2024)
Transition metal sulfides (TMSs) are considered as attractive materials in the areas of energy storage because of their unique redox properties, excellent electronic conductivity, as well as environmental friendliness. However, poor cyclic stability and limited electrochemical active sites hinder their further application. To address this issue, a flower-like hierarchical CuCo2S4 structure is constructed by a two-step hydrothermal method. In this nanostructure, CuCo2S4 grows outward to form a tightly bound hierarchical structure on the nickel foams (NFs). This oriented structure can provide more laminar gaps for electrolyte ion diffusion, exposing more reaction sites to increase the ion transport efficiency between the layers, reducing the ion transport resistance and improving the reaction kinetics. Thus, the CuCo2S4 electrode exhibits excellent energy storage performance, exhibiting a high specific capacity of 1415.6 F g−1 at 1 A g−1. After 10,000 cycles of 10 A g−1, it still has 91.9% of the initial performance. In addition, an asymmetrical supercapacitor (ASC) was constructed by choosing CuCo2S4 as the anode and RGO as the cathode, which has the maximum energy density (61.8 Wh Kg−1) at 812.1 W Kg−1 and significant cycling endurance (92.05% retention) at 10,000 turns. Briefly, the researchers successfully constructed an array of CuCo2S4 flower-like hierarchical nanostructures and confirmed their potential application in supercapacitors.